Evaluating Midazolam’s Influence on Bispectral Index and Propofol Concentrations Using Schnider and Eleveld Models in Target-Controlled Infusion General Anesthesia: A Prospective Observational Study - Federico Linassi; Paolo Zanatta; Matthias Kreuzer; Emma Ciavattini; Christian Rizzetto; Michele Carron (Life)
Background: Midazolam is widely used in clinical anesthesia, but its effects on the Bispectral Index (BIS) and propofol concentration at the effector site (CeP) are underexplored. This study investigates the pharmacodynamic interaction between midazolam and propofol in total intravenous anesthesia (TIVA) with target-controlled infusion (TCI), focusing on Schnider and Eleveld models. Methods: This prospective study included breast surgery patients receiving TIVA-TCI. BIS and CeP were assessed at loss of responsiveness (LoR), during maintenance (MA), and at return of responsiveness (RoR). Incidences of unwanted spontaneous responsiveness (USRE), burst suppression episodes (BSuppE), and postoperative delirium (POD) were recorded. Results: Midazolam premedication significantly reduced propofol doses and CeP at LoR and during MA, without affecting CeP at RoR. In the Schnider model, midazolam reduced total propofol dose, while in the Eleveld model, it lowered BIS at LoR. Unwanted anesthesia events occurred in 36.2% of patients, including USRE (10%), BSuppE (26.2%), and POD (1.2%). BSuppE rates were lower in the Schnider model and reduced in the midazolam group in the Eleveld model. Conclusions: Midazolam premedication influences CeP and BIS in TIVA-TCI, with model-specific variations, optimizing propofol management and improving patient outcomes.